ANALISIS DAMPAK PANDEMI COVID-19 TERHADAP PERUBAHAN STRUKTUR PEREKONOMIAN DI KABUPATEN NATUNA - Nur Indah Wulan; Ahmad Syukron Prasaja (Jurnal Ekonomi & Bisnis, 2023)
This study aims to see the success of economic development in a country, you can take advantage of the growth of the Gross Regional Domestic Product (GRDP) from various industries. Regional Gross Domestic Product (GRDP) is one of the factors that can be used to determine the economic level of a country or region, at current prices and constant prices. This Gross Regional Domestic Product (GDP) growth occurs if the area has a leading sector or a base sector with a relatively fast growth rate. This study uses time series data from the Riau Archipelago Province Central Statistics Agency (BPS) from 2018 and 2022. The purpose of this research is to identify the impact of the Covid-19 pandemic on the Natuna Regency area between 2018 and 2022. 2018 was taken before the Covid-19 Pandemic and 2022 is taken after the Covid-19 incident. This is done using the location quotient analysis method and the dynamic location quotient (DLQ) method. The results of this study indicate that there are several sectors that experience performance delays and there is no change before Covid-19 or after Covid-19, this is due to large-scale social restrictions imposed by the government due to Covid-19. However, there are several sectors that fall into the potential category and are not affected by Covid-19 so that they are feasible to develop, namely the agriculture, forestry and fisheries sectors, the mining and quarrying sector, and the corporate services sector.